Group projects as spaces for leadership development in the liberal arts classroom: a case of American undergraduate students - Almazovaite, Marta; Cohn, Erin Park; Kumar, Sirohi (Frontiers in Education, 2024)
Institutions of higher education almost universally promise to produce society’s future leaders and changemakers. However, collegiate leadership programs are often more attractive and accessible to students from dominant backgrounds, resulting in a lack of diversity. Further, students participating in formal collegiate leadership programming, whether curricular or co-curricular, are frequently taught a one-size-fits-all style of leadership that focuses on individual traits and skills and fails to teach students how to facilitate change with real groups of complex and diverse human beings. This study explores the ways in which undergraduate students gain powerful collaborative leadership skills and begin to redefine leadership via an alternate route in their college experience: applied group projects embedded in disciplinary liberal arts courses. Such projects give students a chance to redefine leadership for themselves, and practice a style of leadership that is more adaptable, contextually embedded, power-aware, and non-hierarchical. We term this “small-l” leadership. In this case study, we explore the role of collaborative group projects in the development of “small-l” leadership through a qualitative study driven by grounded -theory methodology followed by a thematic analysis. Through a series of individual and oral interviews with 18 undergraduate students enrolled in 10 distinct courses at a small liberal arts college, we find that long-term collaborations in classrooms help students: (1) develop heightened sensitivity and skill in navigating group dynamics, (2) gain consciousness of how to navigate their own agency in relation to that of the group, and (3) begin to adopt a more expansive definition of leadership. We determine that with a handful of small interventions, instructors can significantly enhance “small-l” leadership learning through group work. Altogether, our findings illustrate how collaborative learning in liberal arts classrooms can meaningfully contribute to the development of leaders who impact the world around them by co-creating with others across disciplines and differences.